SIMULATION OF VALUES OF COMPANY’S INTELLECTUAL CAPITAL AS A SYSTEM-FORMING FACTOR IN ITS COMPETITIVENESS - Останкова, Лариса; Шевченко, Наталья; Гетьман, Марина (International Journal of Economic Practice and Policy, 2015)
The relevant problems of assessing the value of intellectual capital are examined in this paper. A simulation model for evaluating intellectual capital is constructed on the basis of the Monte-Carlo method. A statistical analysis of the results of simulation is conducted.